Existence of Solutions for Fractional Integro-Differential Equations with Impulsive and Integral Conditions (Journal of Nonlinear Modeling and Analysis, 2024)
This paper presents the existence of solutions for a class of Cauchy problems with integral condition for impulsive fractional integro-differential equations. Based on definition of solution for impulsive fractional integro-differential equations, the existence theorems of solutions of fractional differential equation are obtained by applying fixed point methods. Finally, three examples are given to demonstrate the feasibility of the obtained results.
Keywords: Existence of solutions; impulsive fractional differential equations; fixed point theorems.